Pelatihan Digital Skill Guna Meningkatkan Market Bagi Pengusaha UMKM - Wati, Lela Nurlela; Soma, Mukti; Mulyanti, Rita Yuni; Santoso, Imam; Supriatininingsih, Supriatiningsih (Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this service is to provide training on how to improve the quality of MSME human resources by improving social media-based marketing using digital skills. This training was carried out by the community service team at the Muhammadiyah University of Technology Jakarta in collaboration with the Telkom Community Development Center Bandung. Through this training, it is hoped that MSMEs will understand and master digital technology. Training is held offline through lectures and discussions on digital concepts. The use of digital is expected to grow a social network without limits. MSME stakeholders can find out the benefits of social media-based marketing such as WhatsApp, Instagram, Facebook, Telegram, Twitter, and others so that MSME products offer more opportunities to expand business networks and increase sales.